Systematic Review: Mencegah dan mengobati Overweight dan Obesitas pada Masa kanak-kanak - Jevin Anugrah Saputra; Nur Alam Fajar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The prevalence of childhood obesity is increasing worldwide with long-term health consequences. Effective strategies are needed to prevent rising obesity rates, but systematic reviews of interventions have reported inconsistent impact. Evaluation of interventions can provide more practically relevant information when considered in the context of the situation in which the intervention is implemented. This systematic review has evaluated dietary and physical activity interventions aimed at reducing childhood obesity, from birth to age 5 years, across intervention settings. These studies were grouped based on the circumstances in which the intervention was carried out, which included interventions in daycare/school (n=5), home (n=3), community (n=2), hospital (n=1), e-health ( n=2). Home-based interventions were identified as the most effective measures as four of five studies reported significant changes in child weight outcomes. Interventions carried out at home and involving parents/family are effective in preventing childhood obesity. These findings should be considered when developing optimal strategies for the prevention of childhood obesity.